Game audio programming 4 : principles and practices - Somberg, Guy, ....- (Boca Raton : CRS Press, Taylor & Francis Group, an informa business, 2024)
Welcome to the fourth volume of Game Audio Programming: Principles and Practices – the first series of its kind dedicated to the art, science, and craft of game audio programming. This volume contains 17 chapters from some of the top game audio programmers in the industry and dives into subjects that apply to diverse game genres and from low-level topics such as thread-safe command buffers and pitch detection to high-level topics such as object management, music systems, and audio tools.
Keywords: Programming